The Distribution of Some Mental Disorders in Population of Young Men and Women - Kron, Leposava; Hošek, Ankica; Momirović, Konstantin (Zbornik Instituta za kriminološka i sociološka istraživanja, 2005)
The differences in distribution of some mental disorders in population of young men and women were analyzed on the basis of data obtained by tests that estimate cognitive and conative functions assumed by cybernetic model of cognitive and conative functioning, disturbance of socialization process and intensity of manifest symptoms of aberrant behavior. The random sample consisted of 1334 subjects, age of 18, 667 male and 667 female. These subjects were classified by iterative application of linear classificators that have preciseness of recognition of 0.997 in full and 1.00 in intragroup space. Applied algorithm has found that there is a set of almost 29% of cognitively and conatively normal subjects with somewhat heighten level of activity and above average efficiency of parallel processor, set of 22% of very stupid subjects, seemingly tame but with feeble efficiency of conative regulators, set of about 16% of those with antisocial disorders of personality, i.e. psychopaths and set consisted of over 32% of anxious neurotics which, however, have above average efficiency of cognitive processors and because of that, good academic achievement. The distribution of subjects of different sexes in this taxons was very uneven. In taxon of well socialized subjects with above average efficiency of all conative regulators, somewhat heighten level of activity, average efficiency of perceptual and serial, but above average efficiency of parallel processor, that is, among subjects with efficient functions of predominantly biological cognitive processors and conative regulators were 37% of men and 20% of women. In taxon that consisted of subjects with inferior functions of cognitive processors and under average efficiency of conative regulators, and because of that not so well level of socialization, there were about 32% of female and only about 13% of male subjects. In the third, in essence psychopathic taxon, there were about 26% of male and only about 6% of female poorly socialized and aggressive subjects which had distinct symptoms of aberrant behavior and poor adaptation to school environment. In the forth taxon, which consisted of above average intelligent, but somewhat neurotic subjects, there were almost 41% of women and almost 24% of men. Relations between sex and falling to certain taxon were significant but asymmetrical: on the basis of belonging to taxons could be inferred about a subject’s sex two times better then it could be predicted to which psychological type subject belongs on the basis of information on his sex.